The imagined itch: brain circuitry supporting nocebo‐induced itch in atopic dermatitis patients. Issue 11 (10th September 2015) - Napadow, V.; Li, A.; Loggia, M.L.; Kim, J.; Mawla, I.; Desbordes, G.; Schalock, P. C.; Lerner, E. A.; Tran, T. N.; Ring, J.; Rosen, B. R.; Kaptchuk, T. J.; et al.
Abstract Background Psychological factors are known to significantly modulate itch in patients suffering from chronic itch. Itch is also highly susceptible to both placebo and nocebo (negative placebo) effects. Brain activity likely supports nocebo‐induced itch, but is currently unknown. Methods We collected functional MRI (fMRI) data from atopic dermatitis (AD) patients, in a within‐subject design, and contrast brain response to nocebo saline understood to be allergen vs open‐label saline control. Exploratory analyses compared results to real allergen itch response and placebo responsiveness, evaluated in the same patients. Results Nocebo saline produced greater itch than open saline control (P < 0.01). Compared to open saline, nocebo saline demonstrated greater fMRI response in caudate, dorsolateral prefrontal cortex (dlPFC), and intraparietal sulcus (iPS) – brain regions important for cognitive executive and motivational processing. Exploratory analyses found that subjects with greater dlPFC and caudate activation to nocebo‐induced itch also demonstrated greater dlPFC and caudate activation, respectively, for real allergen itch. Subjects reporting greater nocebo‐induced itch also demonstrated greater placebo reduction of allergen‐evoked itch, suggesting increased generalized modulation of itch perception. Conclusions Our study demonstrates the capacity of nocebo saline to mimic both the sensory and neural effects of real allergens and provides an insight to the brain mechanisms supporting nocebo‐induced itch in AD, thus aiding our understanding of the role that expectations and other psychological factors play in modulating itch perception in chronic itch patients.